Analisa Pemeliharaan Mesin Produksi dengan Metode Reliability Centered Maintenance (RCM) dan Age Replacement - Juwandono, Joko Tri; Purnama, Jaka (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
Maintenance is needed to keep a machine operating under normal conditions for a certain period of time. PT. Daesang Ingredients Indonesia produces its packaging at a printing plant with the help of rotogravure printing, laminating and slitting machines. A total downtime of 21,100 minutes was obtained from March 2021 to March 2023, resulting in a decrease in production and an increase in costs due to corrective machine maintenance. This study aims to provide preventive maintenance proposals by identifying critical components and optimal maintenance actions using the Reliability Centered Maintenance (RCM) method and formulating component replacement intervals to minimize downtime with Age Replacement. Based on the research results, it is known that the critical components are the bearing, vanbelt and slitting blade components with time direct optimal maintenance measures, while the hose components and impression rollers are condition direct. The formulation of the replacement interval for the bearing, vanbelt and impression roller printing machine components is 23,000 minutes, 49,000 minutes and 47,000 minutes. For bearing components, hoses and vanbelt laminating machines for 28,000 minutes, 35,000 minutes and 44,000 minutes. As for the components of the slitting blade, bearing and vanbelt slitting machine 80,000 minutes, 120,000 minutes and 150,000 minutes